2016
DOI: 10.1186/s12957-016-0931-4
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of the effect of adjuvant radiotherapy on outcomes and complications after radical hysterectomy in FIGO stage IB1 cervical cancer patients with intermediate risk factors (GOTIC Study)

Abstract: BackgroundThere are no definitive criteria for identifying which patients with The International Federation of Gynecology and Obstetrics (FIGO) stage IB cervical cancer will benefit from adjuvant therapy after radical hysterectomy. The aims of this study were to clarify the efficacy of adjuvant therapy and assess complications after radical hysterectomy in patients with FIGO stage IB1 cervical cancer with intermediate risk factors.MethodsBetween January 2005 and December 2009, the medical records of 75 stage I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
29
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(30 citation statements)
references
References 23 publications
0
29
1
Order By: Relevance
“…For example, Nakamura et al . suggested that lymphedema was significantly more common in patients who received RT or CCRT after radical hysterectomy . Other investigators also showed postoperative obstruction was significantly more frequent in patients who received RT after surgery .…”
Section: Discussionmentioning
confidence: 99%
“…For example, Nakamura et al . suggested that lymphedema was significantly more common in patients who received RT or CCRT after radical hysterectomy . Other investigators also showed postoperative obstruction was significantly more frequent in patients who received RT after surgery .…”
Section: Discussionmentioning
confidence: 99%
“…Like in EC, post-operative radiotherapy is associated with a higher risk of LLL (13,14,15,39,40,46,47,48), and the number of removed lymph nodes (40,49) and suprafemoral node dissection seem to be associated with a higher rate of LLL (47).…”
Section: Incidencementioning
confidence: 99%
“…Studies by Kazuto Nakamura and others have shown that radiotherapy can reduce local recurrence rates directly by reducing the tumour diameter and reducing the risk of deep cervical stromal invasion. [18].…”
Section: Discussionmentioning
confidence: 99%